The objectives of the research entitled “Myth in Political News’s Reporting on Yingluck Shinawatra” are (1) to study text signification in political news’s reporting, (2) to examine and disentangle truth from myth in text from political news’s reporting. - ขันธุวาร วาลี (Journal of Management Science Chiangrai Rajabhat University, 2018)
The objectives of the research entitled “Myth in Political News’s Reporting on Yingluck Shinawatra” are (1) to study text signification in political news’s reporting, (2) to examine and disentangle truth from myth in text from political news’s reporting. The study results reveal text signification through various signs with signifiers. This study also finds that the presence was not the absolute truth because there was differance which resulted in absence. The differance was opposite to the presence as reflected in the trace of the meaning. The absence could be studied through this trace which demonstrated and completed the missing meaning. In other words, this absence is the truth. The studied truth was used to disentangle myth from text. Six topics of myth emerged in the study results: (1) representation in politics myth, (2) public interest myth, (3) class myth, (4) myth of patron-client political system, (5) heroine myth, and (6) reconciliation myth.